Perception and compliance to COVID-19 vaccine uptake among public transport users in Kiambu county - Kimeu, Dorothy Kamene; Oyore, John P.; Gitahi, Mary (International Journal of Research in Medical Sciences, 2026)
Background: The COVID-19 was declared a pandemic in 2020 and has so far affected 231 countries, causing over 700 million infections and approximately 7 million fatalities globally. The disease created a heavy burden and disorganized healthcare systems worldwide, with more serious pressure being felt in the African developing countries. Covid’s effects were felt at all levels of society, with serious implications for social, economic, educational, political, and human security. Since there is no known cure for COVID-19, creating immunity is key to prevent future morbidities and fatalities, through vaccination. Methods: A cross-sectional study design to collect data from public transport users. Dependent variable was COVID-19 vaccine uptake, influenced by knowledge, perception, contextual, and socio-demographic factors. Kiambu County was selected purposively. Study population comprised consenting adults using public transport users. A multi-stage sampling approach was used where Kiambu County was first purposively selected, followed by simple random sampling of three sub-counties. Finally, simple random sampling of individual respondents. Data was collected through questionnaires, with 311 questionnaires being analyzed using SPSS 26.0 software. Results: The proportion of public transport users who received the first dose of COVID-19 vaccine is 69.77% males and 30.23% females. Overall, 62.7% of the respondents complied with the first dose of the COVID-19. Overall, 23.15% of the total respondents complied to the complete COVID-19 vaccine uptake. Conclusions: The findings showed a slightly lower average second-dose vaccination rate among males and a general decline in vaccination uptake among older age groups.